Obstetric Outcome of Induction of Labour in a Tertiary Hospital in Nigeria: A Five-Year Retrospective Cross-Sectional Study - Ugwuoroko, Harrison Chiro; Eleje, George Uchenna; Okafor, Chigozie Geoffrey; Okechukwu, Zebulon Chiawolamoke; Eke, Ahizechukwu Chigoziem; Okoro, Chukwuemeka Chukwubuikem; Okafor, Lazarus Ugochukwu; Okafor, Chidinma Charity; Ogabido, Chukwudi Anthony; Njoku, Tobechi Kingsley; et al. (International Journal of Innovative Research in Medical Science, 2023)
Background: Induction of labour has remained one of the most valuable interventions in obstetric practice. Over the years, the proportion of women undergoing induction of labour (IOL) has been on a steady increase. The significance to obstetrics practice as well as its maternal and perinatal outcomes are sacrosanct, hence the need for its periodic review. Objective: To determine the obstetric outcomes of induction of labour. Methods: A five-year retrospective study of all cases of induction of labour at the maternity unit of Nnamdi Azikiwe University Teaching Hospital (NAUTH), Nnewi, Nigeria between January 1st 2017 and 31st December 2021. The labour ward’s records were assessed to determine the total number of women who had induction of labour during the study period. Women whose case files could be not retrieved were excluded. The folder numbers of the patients were extracted and their case files retrieved from the medical records department of the hospital. The primary outcomes measures were the indications and the methods of induction of labour, while the secondary outcome measures were the mode of delivery, cause of failed induction, and the perinatal outcome. Data were obtained using proformas and analysed using statistical packages for social sciences (SPSS) version 26.0 IBM corporation. Result: A total of 3,638 deliveries were taken during the period under review and 168 patients had induction of labour giving an overall prevalence of 4.6% (46/1000 deliveries). Induction of labour was successful in 71.2% of cases. Misoprostol was used in 90.4% of cases as an induction agent. The commonest indication for induction of labour was postdate pregnancy (53.8%). Failed induction was due to fetal distress, poor progress of labour from cephalopelvic disproportion/malposition and failed cervical ripening. In about 72% of deliveries, there was good perinatal outcome, 10.3% of babies had moderate to severe asphyxia while 1.3% had neonatal death. Conclusion: Induction of labour is a safe and beneficial procedure in obstetrics. However, it can be associated with adverse obstetric outcomes.